Avaliação de um protótipo de coletor solar no Semi-árido Potiguar - Pinheiro, Rita de Cássia Cordeiro de Sousa (Universidade Federal Rural do Semi-Árido, 2019)
Brazil is a country that has high incidence of solar radiation, which allows the use of the solar energy as alternative fountain which has been researched and used with many advantages. In this work presents the construction of a prototype of solar collector for the use as air heater with the objective to measure and to search the best configuration for the temperature profit. Also the instrumentation was done for the monitoring of temperature in order to look for the best conditions of functioning of the air heating collector. The monitoring of the temperatures was done along the whole collector where the air flow passes and the temperatures profit was reviewed using alternatives of internal revetment and of covering of the collector, besides the variations in the forced ventilation system. The exit temperatures of the solar collector were analyzed, when temperature peaks are obtained in the exit with value of until 72,5 ºC using a black surface in the interior of the box collector. With the obtained and analyzed results it was possible conclude that the best performance for the developed solar collector was exactly with the black and matte internal revetment, with the glass plate like covering and with the least functionality of the forced ventilation system controlling the flow of heated air, hitting a temperature profit of 79,45 %. It was observed that the best time of exposition of the solar collector in the sun is between 10 h and 15 h due to variation of the incident radiation during the day, what it is the origin of the profit of temperature.
Monografia
Keywords: Energia solar; Coletor solar; Aquecedor de ar; Revestimento preto; Solar energy; Solar collector; Air heater; Black revetment; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA